The representation of female characters in Turkish tv series in the 2010s: how Neo-Ottomanism changed the depiction of women? - Görk, Ekin Deniz (İstanbul Bilgi Üniversitesi, 2022)
ABSTRACT : During the early years of the republic, Turkish state tried to cut off its ties with Ottoman past, but it couldn't succeeded. Instead, Ottoman nostalgia grew within the public and started to show its effects on the cultural and daily products, beginning from the late 1970s. This nostalgia later named as neo-Ottomanism and re-defined with almost every other administration, since each of them approaches to the Ottoman past differently. When 2002 staged to the victory of AKP (Adalet ve Kalkınma Partisi - Justice and Development Party), a political Islamist right wing party, the official attitude against to Ottoman Empire started to change once again. By the date of this study completed––2022––, the party is close to celebrate its 20th anniversary in power. After the six election victories in a row within the twenty years, AKP has managed to built its own era in both the political and cultural history of The Republic of Turkey. As being one of the powerful emotional motive of the period, neo-Ottomanism effected television contents along with many other cultural mediums. Therefore Ottoman-themed television series became a sub-genre in Turkish television dramas, and the decade of 2010s, staged big number of Ottoman-themed television series. This dissertation visually analyzes television series which are based on this Ottoman nostalgia. It uses textual analysis on the three television dramas from the decade of 2010s, Muhteşem Yüzyıl (2011-2014), Muhteşem Yüzyıl: Kösem (2015-2017), Payitaht Abdülhamid (2017-2021), and examines the depiction of women in realms of these series. By using the genre theory, it claims the depiction of women in those series which are created with the neo-Ottomanist nostalgia, changed from using the orientalist iconography to using a new iconography within this decade.

ÖZET: Cumhuriyetin erken yıllarında Türk devleti, Osmanlı geçmişiyle olan bağlarını kesmeye çalıştı, ancak bu konuda başarılı olamadı. Onun yerine halk arasında Osmanlı nostaljisi büyüdü ve geç 1970'lerden başlayarak kültürel ve günlük ürünlerde etkisini göstermeye başladı. Bu nostalji daha sonradan yeniOsmanlıcılık olarak adlandırıldı ve herbiri Osmanlı geçmişine farklı şekilde yaklaştığından neredeyse her yeni hükumetle bu terim yeniden tanımlandı. 2002 yılı siyasal İslamcı sağ kanat bir parti olan AKP'nin zaferine sahne olurken Osmanlı İmparatorluğu'na karşı olan resmi tutum bir kez daha değişmeye başladı. Bu çalışmanın tamamlandığı tarih itibariyle––2022––, parti, yönetimdeki yirminci yılını kutlamaya yaklaşmış bulunuyor. Bu yirmi yıl içerisinde peş peşe altı seçim zaferinden sonra, AKP, Türkiye Cumhuriyeti'nin hem politik tarihinde hem de kültürel tarihinde kendi devrini inşa etmeyi başardı. Bu dönemin oldukça güçlü duygusal motiflerinden biri olan yeni-Osmanlıcılık, birçok farklı kültürel mecranın yanısıra televizyon içeriklerinde de etkisini gösterdi. Bu sebeple Osmanlı temalı diziler Türk televizyonunda bir alt-janr olarak yer edinirken, 2010'lar oldukça fazla sayıda Osmanlı temalı diziye ev sahipliği yaptı. Bu tez, bahsi geçen Osmanlı nostaljisi içerisinde üretilmiş televizyon dizilerinin görsel analizini yapmaktadır. 2010'lu yıllardan üç dizi olan, Muhteşem Yüzyıl (2011-2014), Muhteşem Yüzyıl: Kösem (2015-2017), ve Payitaht Abdülhamid (2017-2021) dizilerine tekst analizi yapmakta ve dizilerin yarattığı evren içerisindeki kadın tasvirini incelemektedir. Tür analizi metodolojisini kullanarak yeni-Osmanlıcılık akımı içerisinde üretilmiş bu dizilerdeki kadın tasvirinin, 10 yıllık süreç içerisinde orientalist ikonografiden, kendine has bir ikonografiye büründüğünü öne sürmektedir.
2010'lu yıllarda yapılmış Türk televizyon dizilerinde kadın karakterlerin temsili: Yeni-Osmanlıcılık kadın tasvirini nasıl değiştirdi?
Keywords: Tür analizi; Yeni-Osmanlıcılık; Oryantalizm; Türk televizyon dizileri; Kadın temsilleri; Genre analysis; Neo-Ottomanism; Orientalism; Turkish television series; Women representations